Political discourse as practical reasoning: A case study of a British Prime Minister candidate speech - Lucyna Harmon (LingBaW)
The paper outlines the method of political discourse analysis proposed by I. Fairclough & N. Fairclough (2012), who point to argumentative and deliberative nature of political discourse as practical reasoning that aims to decide a problem-solving action in a given situation. The novelty of this approach is explained through references to its established alternatives as focused on representation and power relations. The above mentioned method is applied to the British PM campaign candidacy speech by Andrea Leadsom to test how it works in the case of this type of political discourse which is different from the one originally examined. On this occasion, the meaning of the term ‘discourse’ is illustrated through the practical necessity of involving in the analyses the extra-linguistic and intertextual context.